Landau-Kleffner syndrome - Campos, José Guevara; de Guevara, Lucía González (Journal of Pediatric Neurology, 2007)
We reviewed the etiology, clinical symptoms, differential diagnosis, treatment and prognosis of the Landau-Kleffner syndrome. The Landau-Kleffner syndrome is a rare syndrome of unknown etiology. Onset occurs between 18 months and 13 years of age, with three-fourths of the cases appearing before the age of 7 years. Most patients appeared normal before the onset of the syndrome. The loss of acquired language is usually total, but nonverbal skills are generally completely or at least relatively preserved. Clinical seizures are experienced by 70% of patients at some time, although they do not necessarily appears at very beginning of disorder. Paroxysmal electroencephalography abnormalities are often very marked; such abnormalities tend to increase during slow wave sleep, often producing continuous spike and waves during slow wave sleep. Other characteristics associated with this syndrome include neurobehavioral symptoms such as autistic behavior, various degrees of cognitive regression and motor disorders. Treatment with standard anti-epileptic drugs is typically not effective. Adrenocorticotropic hormone is currently preferred due to its clinical and electroencephalographic efficacy. The prognosis is uncertain. Significant improvement is observed in most cases, although moderate or permanent speech deficiencies typically persist. Since proper treatment of Landau-Kleffner syndrome, once identified, can have profound consequences on a child's language development, it is important for the clinician to evaluate any child with alterations of speech development without a cause with an electroencephalogram that includes recording during sleep.
Keywords: Landau-Kleffner syndrome; epileptic aphasia; adrenocorticotropic hormone; autism